Study on Dynamic Characteristics of Parabolic Trough Solar Collector Circuit - Lanhua LIU; Linwen DI; Xingwan DONG; Ruilin WANG (发电技术)
The solar radiation is intermittent and unstable, and its dynamic instability affects the stable output of parabolic trough solar collector. Therefore, it is extremely important to study the dynamic characteristics of the solar heating process of parabolic trough solar collector. The dynamic simulation model of parabolic trough solar collector one-dimensional loop was constructed based on the Simscape environment in MATLAB/Simulink software. Based on the verified dynamic simulation model, the influence of mass flow and direct normal irradiance on the outlet temperature of the loop of parabolic trough solar collector was obtained. According to the obtained law, the dynamic regulation model of the loop of parabolic trough solar collector was constructed based on the proportional integral. The results show that the control strategy can make the outlet temperature of the loop reach the set temperature of 395 ℃ within 2 500 s when the direct normal irradiance increases suddenly, and maintain the output temperature fluctuation within -2 ℃ to 2 ℃ when the direct normal irradiance decreases suddenly. Based on the dynamic regulation strategy, the operation of the loop of parabolic trough solar collector in typical day was simulated. The results show that the regulation strategy can maintain the outlet temperature of the loop in the operation time and the thermal efficiency close to the ideal value. The study provides a new method for the construction of dynamic model of the parabolic trough solar collector, and the results can provide reference for the dynamic operation of the parabolic trough solar field.